Motivasi Dalam Aspek Pemilihan Profesi Sebagai Karyawan Bank Syariah X Surabaya (Studi Kasus Rekrutmen Tahun 2012) - Andriani, Eka Rizky; Faiza, Siti Inayatul (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
Developing the rapid syariah banking along with increasing number of employee who is recruited by syariah banks motivate human resources existing to choose profession as employees in syariah banks.This research aims to know the basic considerations motivation for choosing a profession as an employee of Bank Syariah X Surabaya. The approach used in this research is qualitative approach with eksplanatoris case study. . Data collection is done by gathering documents, interviews, direct observation, and physical devices toward employee recruitment of Sharia Bank X Surabaya 2012. The techniques of analysis conducted is making an explanation.The results obtained that there are various forms of motivation shown by each employee who push their chosen profession as an employee of Bank Syariah X Surabaya. Then, that motivation is classified and described according to the theory of motivation based on Islam, Khaliq Ahmad namely The Need Theory, Instincts and Innate Biological Determinants for Behaviour, Incentives (External Stimuli),Commitment (Sincere), and Motivated Personality which is separated as Nafs Ammarah, Nafs Lawwamah, and Nafs Mutmainnah.